Voluntary Restraint Sebagai Hukum Untuk Membatasi Penggunaan Hak Veto Negara dalam Kasus Penyelesaian Mass Atrocity - Jacobus, Chris Emilians; de Sousa, Freidelino Paixao Ramos Alves (Widya Yuridika, 2025)
This research objective is to analyze Voluntary Restraint as a legal concept to limiting the veto used by P5 countries of United Nation Security Council (5 permanent member of UNSC) in settlement of mass atrocity case. This research is a normative juridical research that used conceptual and historical approach. Veto is used by P5 countries only for their benefits and national interest, even in cases that are clearly a serious violation of principles in UN and International community, and because of that the used of veto  must be limited. Voluntary Restraint is a legal concept that essentially limits or prohibits the veto use, especially in mass atrocity cases and this is in line with Jus Cogens principle, which is the peremptory norm that has been agreed by the international community including by the P5 countries. The findings of this research are that Voluntary Restraint is a Law itself and as a manifestation of the Jus Cogens principle. Ideally this concept should be a written norm in the UN charter, but this concept can be implemented or not is back to the commitment about world peace, international security and respect of Human Rights from the P5 countries itself.